Social Media Optimization Strategy to Strengthen Teacher Professionalism in Islamic Educational Institutions - Ahmad Septian Alghifari; Marno (Managere: Indonesian Journal of Educational Management, 2025)
This study examines social media optimisation strategies for enhancing the professionalism of teachers in Islamic educational institutions in Gresik Regency. Using a qualitative approach with a case study design, data were collected through in-depth interviews, document searches, and field findings. The results of this study show that teachers utilise various social media platforms, including WhatsApp for communication and coordination, Facebook for professional community development, and YouTube for creating and disseminating educational content. However, this implementation faces significant challenges, including the risk of spreading negative information, a lack of digital literacy among some teachers, and resistance to technology. To overcome these barriers, educational institutions have implemented proactive strategies that include digital literacy training,  content creation workshops, learning community development, periodic evaluations, and collaboration with parents. Therefore, the research provides implications that emphasise the urgency of formulating adaptive policies and providing ongoing, practical support to develop digitally competent and ethically based teaching staff.